A comparison of methods for gene dosage analysis in HMSN type 1. Issue 2 (1st February 2001) - Rowland, Jayne S; Barton, David E; Taylor, Graham R; ,
Abstract : A number of different approaches are used in diagnostic laboratories to detect the 1.5 Mb duplication at 17p11.2 seen in approximately 70% of patients with hereditary motor and sensory neuropathy type 1 (HMSN1). Here we compare the methods used in UK diagnostic laboratories to detect the duplication. Samples referred to participating centres for HMSN testing were collected, randomised, and distributed for testing. One hundred samples were examined using five different methods; each method was tested by two independent laboratories. Identical results were obtained from all laboratories for 44 samples. The remaining samples were classified as duplication positive or duplication negative on the basis of the same result by two or more methods. A total of 95 samples were classified by more than one method, two were withdrawn from the study as the same result was not obtained by two methods, and three are thought to have a duplication smaller than 1.5 Mb. Seven of 49 duplications were not detected by methods used to detect the common junction fragment and the use of microsatellites failed to yield a result in four of 95 samples. Sequence tagged site (STS) dosage analysis was found to be the most sensitive of the methods tested, although this method was found to be the most likely to require repeat analysis. Eight samples gave discordant results between the two laboratories testing by the same method. Upon retesting, reasons for the initial incorrect result included processing and typographical errors.